Nosema ceranae infection in honeybee samples from Tuscanian Archipelago (Central Italy) investigated by two qPCR methods - Giovanni Cilia (Saudi Journal of Biological Sciences, 2019)
Nosema apis and Nosema ceranae are microsporidian parasite worldwide spread causing an emerging infectious disease of European honeybee Apis mellifera. The Nosema presence was deeply investigated in several countries but low information are presents about islands. In this investigation was evaluated the presence N. ceranae and N. apis in apiaries located in Tuscanian Archipelago islands (Central Italy). For N. ceranae detection, two different Real-Time PCR (qPCR) methods, the 16S rRNA and Hsp70 gene amplification qPCR, were performed on honey bee samples; while, for N. apis only the 16S rRNA qPCR amplification was performed. On all islands, only N. ceranae was present, while N. apis was not found in the samples. The two qPCR showed significant difference (p < 0.040) in N. ceranae spores quantification. The single-copy Hsp70 gene method qPCR assay systematically detected a lower amount of N. ceranae copies compared to the multi-copy 16S rRNA gene method. Keywords: Nosema ceranae, Nosemosis, qPCR, Hsp70 and 16S rRNA gene, Apis mellifera, Tuscanian Archipelago